2005
DOI: 10.1208/pt060238
|View full text |Cite
|
Sign up to set email alerts
|

Process analytical technology case study: Part II. Development and validation of quantitative near-infrared calibrations in support of a process analytical technology application for real-time release

Abstract: This article is the second of a series of articles detailing the development of near-infrared (NIR) methods for solid dosage-form analysis. Experiments were conducted at the Duquesne University Center for Pharmaceutical Technology to demonstrate a method for developing and validating NIR models for the analysis of active pharmaceutical ingredient (API) content and hardness of a solid dosage form. Robustness and cross-validation testing were used to optimize the API content and hardness models. For the API cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 18 publications
0
13
0
4
Order By: Relevance
“…NIRS has also been successfully used in a variety of other analytical chemistry applications such as the detection of degradation products in tablets (7); studying drug moisture content over time and water mobility within the drug crystal lattice (8,9); real-time monitoring of moisture during processing using fluidized bed granulation (10,11) or roller compaction (12), measurement of particle size, and size distribution (13)(14)(15); and determining the tablet drug content and content uniformity (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…NIRS has also been successfully used in a variety of other analytical chemistry applications such as the detection of degradation products in tablets (7); studying drug moisture content over time and water mobility within the drug crystal lattice (8,9); real-time monitoring of moisture during processing using fluidized bed granulation (10,11) or roller compaction (12), measurement of particle size, and size distribution (13)(14)(15); and determining the tablet drug content and content uniformity (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…According to the PAT guide, the gains in processes quality, safety, and/or efficiency can be increased depending on the product; these changes come from factors such as the prevention of rejections, the disposal and reprocessing of products, and the possibility of carrying out analysis in real time with reduced or no sample preparation [5,52], leading to a reduction of human error and increasing the safety of the operator, with no risk to the environment [9,10,53]. The PCR model could address most of these factors, because each sample can be irradiated rapidly and examined directly with the use of an optical probe, without prior preparation, to obtain a single spectrum, which minimizes human error.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been carried out to explore the use of NIRS for powder blending control. The fact that NIRS has great potential in this application has been shown by Wargo and Drennen [139][140][141][142]. Cho and co-workers dealt with the effective mass that is sampled by NIR fibre-optic reflectance probes in blending processes and demonstrated that the sampled mass met FDA requirements [143].…”
Section: Powder Blendingmentioning
confidence: 99%